Numerical methods for equations and its applications - 539038 Argyros, Ioannis K.; Cho, Yeol Je; Hilout, Said (Boca Raton : CRC Press)
"This monograph is intended for researchers in computational sciences, and as a reference book for an advanced numerical-functional analysis or computer science course. The goal is to introduce these powerful concepts and techniques at the earliest possible stage. The reader is assumed to have had basic courses in numerical analysis, computer programming, computational linear algebra, and an introduction to real, complex, and functional analysis. Although the book is of a theoretical nature, with optimization and weakening of existing hypotheses considerations each chapter contains several new theoretical results and important applications in engineering, in dynamic economics systems, in input-output system, in the solution of nonlinear and linear differential equations, and optimization problem"--